Chalcone Derivatives From Abelmoschus manihot Seeds Restrain NLRP3 Inflammasome Assembly by Inhibiting ASC Oligomerization - Su, Jinsong; Yang, Fujing; Kang, Xuemei; Liu, Jia; Tao, Yiwen; Diao, Qingchun; Meng, Xianli; Liu, Deming; Zhang, Yi (Frontiers in Pharmacology, 2022)
Three chalcone derivatives, Abelmanihotols A−C (1−3), and nine known compounds were isolated from Abelmoschus Manihot seeds, and their structure were determined using HRESIMS and NMR spectroscopic analysis. Compound 1 exhibited the most potent inhibitory effect (IC50 = 4.79 ± 0.72 μM) against lipopolysaccharide (LPS)-induced NO release in THP-1 cells and significantly inhibited interleukin 1β (IL-1β) secretion, which stimulated by LPS plus nigericin (IC50 = 11.86 ± 1.20 μM), ATP or MSU, in THP-1 cells. Preliminary mechanism of action study indicated that 1 blocked the formation of nucleotide oligomerization domain-like receptor protein-3 (NLRP3) inflammasome formation by suppressing apoptosis-associated speck-like protein oligomerization, thereby attenuating caspase-1 activation and IL-1β release. These results revealed that 1 is not only a potent and efficacious NLRP3 inflammasome inhibitor and but also a promising drug for the treatment of NLRP3-related diseases.